Correlation between magnetic resonance images of peritumor margin enhancement and prognosis in hepatocellular carcinoma after drug-eluting bead transcatheter arterial chemoembolization - Kuang, Donglin; Zhang, Nan; Zhang, Mengfan; Li, Hao; Han, Xinwei; Ren, Jianzhuang; Duan, Xuhua (Frontiers in Oncology, 2023)
To investigate the morphological characteristics and clinical significance of magnetic resonance (MR) images of peritumor margin enhancement in hepatocellular carcinoma (HCC) after drug-eluting bead transcatheter arterial chemoembolization (DEB-TACE). From January 2017 to December 2020, a total of 162 patients who received a diagnosis of HCC were included in our study. We began the follow-up with magnetic resonance imaging (MRI) for complete response assessment, and peritumor margin enhancements were classified as sharp and rough types according to morphology. During the follow-up, data such as progression or remission of the two enhancement modalities, morphological changes in terms of margin enhancements observed in MR images, and alpha-fetoprotein (AFP) levels were recorded. In the follow-up period of 36 months, 70 and 92 patients with sharp- and rough-type peritumor margins, respectively, were observed. At the end of the followup, patients with sharp-type margins had lower AFP levels and longer progressionfree survival than those with rough-type margins (P < 0.05). Furthermore, the sharp- type margin was thinner than the rough-type margin (all P < 0.05). Moreover, the sharp-type group had a high incidence of tumors with a diameter of <5 cm, whereas the rough-type group had a high incidence of tumors with a diameter of ≥5 cm. Continuous enhancements of peritumor margins in MRI were more in the sharp-type group than in the rough-type group. Most of the patients with a sharp-type margin achieved disease remission (94.3%, P < 0.05), whereas most of those with a roughtype margin experienced disease progression (84.8%, P < 0.05). Patients with HCC with a sharp-type margin enhancement in MRI after DEB-TACE mostly demonstrated benign lesions with a good prognosis, whereas those with a rough-type margin mostly demonstrated malignant growth.